The effect of grazing and reclamation on rodent community stability in the Alxa desert - Yuan, Shuai; Zhang, Hao-Ting; Li, Xin; Yue, Xiu-Xian; Fu, He-Ping; Wu, Xiao-Dong (Frontiers in Ecology and Evolution, 2023)
Ecosystem stability has been of increasing interest in the past several decades as it helps predict the consequences of anthropogenic disturbances on ecosystems. A wild rodent community under reclamation and different grazing disturbances in the Alxa Desert was investigated using live trapping from 2006 to 2011. We studied the rodent community composition, community diversity and variability of different life history strategies. These results showed that reclamation reduced rodent community stability by increasing temporal variability of community, reducing rodent community resistance as shown by decreasing dominance of KSS strategists, and increased the resistance variability of the rodent community by increasing the variability of abundance and richness for KSS strategists. Grazing reduced rodent community resilience by reducing the dominance of rRF strategists, and increased the resilience variability of the rodent community by increasing the variability of abundance and richness for rRF strategists. Those results may answer the three ecological questions about how ecosystems respond to disturbances from a diversity perspective. The ecosystems with intermediate disturbance are more stable, in other words, with higher resistance and resilience. The increase of KSS strategists means the increase of resistance of the community. The increase of rRF strategists means the increase of community resilience.